Dynamic Analysis of Planar Mechanism in Numerical Methods - Thanh Nhan Phan (Journal of Technical Education Science, 2024)
In kinematic synthesis and analysis of planar mechanisms the designer must define a geometry and set of motions for a design task. Then it is logical to determine the forces or torques in order to create such motion in the system, which means finding out a convenient approach to solving for the forces and torques that result from our kinematic system in such a way as to provide the designed accelerations. This task is called dynamic force analysis (or kinetic analysis). Many numerical methods to determine the position, velocity, and acceleration of a planar mechanism are introduced and applied successfully, for example, using the transformation matrix. To solve fully kinetic problems for a planar mechanism, it is necessary to establish a simple and easy procedure that determines the forces or torques maintaining the motion in the system with the help of a computer. This paper will focus on how to determine the forces or torques acting on the planar mechanism by numerical method when acceleration and dynamic properties of the linkage are known. Some of the chosen examples shown here aim to demonstrate in detail the numerical solution for dynamic force analysis. The paper’s purpose is not to demonstrate novelty, but to propose a new approach that can be applied to machinery design projects for students. University students can consult the content of this paper to carry out kinematic and kinetic analysis of planar mechanisms using this numerical method, as opposed to the traditional vector drawing method that is widely used.